Deficiency of Intestinal α1‐2‐Fucosylation Exacerbates Ethanol‐Induced Liver Disease in Mice. (2nd August 2020) - Zhou, Rongrong; Llorente, Cristina; Cao, Jinling; Gao, Bei; Duan, Yi; Jiang, Lu; Wang, Yanhan; Kumar, Vipin; Stärkel, Peter; Bode, Lars; Fan, Xuegong; Schnabl, Bernd
Abstract : Background: Fucosyltransferase 2 (Fut2)‐mediated intestinal α1‐2‐fucosylation is important in maintaining a symbiotic host–microbiota relationship and can protect against several pathogens. Intestinal dysbiosis is an important factor for the progression of experimental ethanol (EtOH)‐induced liver disease, but the role of Fut2 in modulating the intestinal glycocalyx during alcohol‐associated liver disease is unknown. We investigated the role of Fut2‐mediated intestinal α1‐2‐fucosylation for the development of alcohol‐associated liver disease. Methods: Immunohistochemistry staining was applied to evaluate α1‐2‐fucosylation in duodenal biopsies from patients with alcohol use disorder. Wild‐type (WT) and Fut2 ‐deficient littermate mice were subjected to Lieber–DeCarli models of chronic EtOH administration and the chronic‐binge EtOH diet (NIAAA model). Results: Intestinal α1‐2‐fucosylation was down‐regulated in patients with alcohol use disorder. Lack of α1‐2‐fucosylation in Fut2 ‐deficient mice exacerbates chronic EtOH‐induced liver injury, steatosis, and inflammation without affecting EtOH metabolism. Dietary supplementation of the α1‐2‐fucosylated glycan 2′‐fucosyllactose (2′‐FL) ameliorates EtOH‐induced liver disease in Fut2‐ deficient mice in the NIAAA model. Despite no direct effects on growth of Enterococcus faecalis in vitro, intestinal α1‐2‐fucosylation reduces colonization of cytolysin‐positive E. faecalis in the intestine of EtOH‐fed mice. Conclusions: Intestinal α1‐2‐fucosylation acts as a host‐protective mechanism against EtOH‐induced liver disease. 2′‐FL is an oligosaccharide naturally present in human milk that could be considered as therapeutic agent for alcohol‐associated liver disease. Abstract : Alcohol abuse is associated with decreased intestinal α1‐2‐fucosylation in patients with chronic alcohol use. Eliminating α1‐2‐fucosylation by using Fut2 deficient mice exacerbates ethanol‐induced liver disease. A dietary approach to restore α1‐2‐fucosylation with prebiotic α1‐2‐fucosylated glycans overcomes the absence of intestinal α1‐2‐fucosylation in Fut2 ‐/‐ mice and attenuates ethanol‐induced liver disease. Our findings emphasize the important role of the intestinal glycocalyx for the pathogenesis of ethanol‐induced liver disease in mice. Intestinal α1‐2‐fucosylation acts as a host protective mechanism against ethanol‐induced liver disease.